Burning Up A Global History of Fossil Fuel Consumption - Pirani, Simon (Pluto Press, 2018)
Coal, gas and oil have been capitalism's main fuels since the industrial revolution. And yet, of all the fossil fuels ever consumed, more than half were burned in the last 50 years. Most alarming of all, fossil fuel consumption has grown fastest in the last three decades, since scientists confirmed that it is the main cause of potentially devastating global warming. In Burning Up, Simon Pirani recounts the history of fossil fuels' relentless rise since the mid twentieth century. Dispelling explanations foregrounding Western consumerism, and arguments that population growth is the main problem, Pirani shows how fossil fuels are consumed through technological, social and economic systems, and that these systems must change. This is a major contribution to understanding the greatest crisis of our time.